Answer:
x = -25
Explanation:
Solve for x:
(2 x)/5 - 6 = -16
Hint: | Put the fractions in (2 x)/5 - 6 over a common denominator.
Put each term in (2 x)/5 - 6 over the common denominator 5: (2 x)/5 - 6 = (2 x)/5 - 30/5:
(2 x)/5 - 30/5 = -16
Hint: | Combine (2 x)/5 - 30/5 into a single fraction.
(2 x)/5 - 30/5 = (2 x - 30)/5:
(2 x - 30)/5 = -16
Hint: | Multiply both sides by a constant to simplify the equation.
Multiply both sides of (2 x - 30)/5 = -16 by 5:
(5 (2 x - 30))/5 = -16×5
Hint: | Cancel common terms in the numerator and denominator of (5 (2 x - 30))/5.
(5 (2 x - 30))/5 = 5/5×(2 x - 30) = 2 x - 30:
2 x - 30 = -16×5
Hint: | Multiply 5 and -16 together.
5 (-16) = -80:
2 x - 30 = -80
Hint: | Isolate terms with x to the left hand side.
Add 30 to both sides:
2 x + (30 - 30) = 30 - 80
Hint: | Look for the difference of two identical terms.
30 - 30 = 0:
2 x = 30 - 80
Hint: | Evaluate 30 - 80.
30 - 80 = -50:
2 x = -50
Hint: | Divide both sides by a constant to simplify the equation.
Divide both sides of 2 x = -50 by 2:
(2 x)/2 = (-50)/2
Hint: | Any nonzero number divided by itself is one.
2/2 = 1:
x = (-50)/2
Hint: | Reduce (-50)/2 to lowest terms. Start by finding the GCD of -50 and 2.
The gcd of -50 and 2 is 2, so (-50)/2 = (2 (-25))/(2×1) = 2/2×-25 = -25:
Answer: x = -25